The Interplay of SIRT1 and Wnt Signaling in Vascular Calcification - Bartoli-Leonard, Francesca; Wilkinson, Fiona L.; Langford-Smith, Alex W. W.; Alexander, M. Y.; Weston, Ria (Frontiers in Cardiovascular Medicine, 2018)
Vascular calcification is a major health risk and is highly correlated with atherosclerosis, diabetes and chronic kidney disease. The development of vascular calcification is an active and complex process linked with a multitude of signalling pathways, which regulate promoters and inhibitors of osteogenesis, the balance of which become deregulated in disease conditions. SIRT1, a protein deacetylase, known to be protective in inhibiting oxidative stress and inflammation within the vessel wall, has been shown as a possible key player in modulating the cell-fate determining canonical Wnt signalling pathways. Suppression of SIRT1 has been reported in patients suffering with cardiovascular pathologies, suggesting that the sustained acetylation of osteogenic factors could contribute to their activation and in turn, lead to the progression of calcification. There is clear evidence of the synergy between β-Catenin and elevated Runx2, and with Wnt signalling being β-Catenin dependent, further understanding is needed as to how these molecular pathways converge and interact, in order to provide novel insight into the mechanism by which smooth muscle cells switch to an osteogenic differentiation programme. Therefore, this review will describe the current concepts of pathological soft tissue mineralisation, with a focus on the contribution of SIRT1 as a regulator of Wnt signalling and its targets, discussing SIRT1 as a potential target for manipulation and therapy